Strategi Global 'the UN Alliance for Sustainable Fashion' dalam Mendorong Industri Fashion Berkelanjutan di Bangladesh (ISJN Journal, 2022)
The emergence of the Fast Fashion phenomenon has an environmental and social impact in the fashion industry. The impact caused by the fashion industry underlies the initiation of the formation of The UN Alliance for Sustainable Fashion. The UN Alliance supports projects and policies that ensure that the fashion value chain contributes to sustainable values. The impact of the fashion industry, especially in Bangladesh, which relies on exports of the garment industry and makes the garment industry sector its main income, has made Bangladesh the second largest global clothing exporter after China and has exported to 132 countries. This study aims to analyze the strategy of the UN Alliance through the efforts of UN agencies as part of the UN Alliance to encourage the fashion industry in Bangladesh to prioritize sustainable values. This study uses qualitative methods and data collection techniques through literature study. In this study the authors use the concept of Sustainable Fashion and International Organizations. This study formulates the strategic findings of the UN alliance in encouraging a sustainable Fashion Industry in Bangladesh, namely by encouraging the implementation of Ethical Fashion, encouraging the use of renewable technologies and clean industries, and also encouraging the formation of norms.